A 3D BEM-FEM approach using layered transversely isotropic half-space Green's functions in the frequency domain for SSI analyses. (1st November 2021) - Mehdizadeh, Delaram; Eskandari-Ghadi, Morteza; Rahimian, Mohammad
Abstract: In this paper, a numerical approach based on a three-dimensional (3D) standard coupled boundary element method-finite element method (BEM-FEM) formulation in the frequency domain is presented. The approach allows studying the dynamics response of a structure bonded to the surface of a layered transversely isotropic half-space subjected to time-harmonic loading. The FEM is used to model the structure, and the BEM is employed for the soil, using layered half-space Green's functions, by which the radiation condition is implicitly satisfied. The BEM procedure is improved by implementing exponentially gradient (EG) elements to capture the singular behavior of tractions at the edges and corners of the soil-structure interface. The proposed approach is verified by comparison with existing semi-analytical and numerical results. Afterward, the dynamic response of a building on a layered transversely isotropic half-space subjected to lateral loading is studied, and the effect of soil layering on the response of the structure and interface tractions is demonstrated.